The role of footwear-independent variations in rearfoot movement on impact attenuation in heel-toe running - Kersting, U. G.; Kriwet, A.; Brüggemann, G. P. (Research in Sports Medicine, 2006)
Impact forces and rearfoot eversion have been linked to overuse injuries in running. Modeling approaches suggest that both factors interact in that reduced foot eversion relates to increased impact maxima and vice versa. The aim of this study was to alter rearfoot eversion by applying three different combinations of ankle taping and bracing. Ten subjects were tested while running at 4 m/s on an instrumented treadmill. Sagittal plane kinematics, rearfoot eversion, tibial acceleration, pressure under the heel, and vertical ground reaction force (GRF) were collected simultaneously over 12 to 14 steps. All interventions reduced the maximum eversion significantly compared with unrestricted running. The largest effect was shown for combined bracing and taping, reducing rearfoot movement by 6.1° while impact force varied only marginally. Overall, relationships between parameters contradict predictions by existing models of foot-ground interaction. Changes in muscular activation remain as a candidate in the regulation of impact mechanics in running.